Understanding Church Growth - Pathil, Kuncheria (Journal of Dharma, 1981)
Donald A. Mc Gavran Understanding Church Growth, Grand Rapids (Michigan): William B. Eerdmans Publishing Company, 1980. pp. xvi + 480.